Obituary: William Mark Whitten (1954−2019) - Blanco Coto, Mario Alberto (2019)
On April 11, 2019, Dr. William Mark Whitten, a prolific neotropical orchid biologist passed away unexpectedly. He leaves an extensive corpus of work focused on (but not limited to) orchid pollination and systematics, and over four thousand beautifully prepared herbarium specimens. Everyone that met Mark can agree that he was a wonderful human being, kind to everyone, incredibly knowledgeable and yet very humble. Always of a calm demeanor, great sense of humor, and willingness to help, Mark was an outstanding and relatable collaborator, and his publications (more than a hundred; see list below) are evidence of a productive and highly collaborative academic career.